AMRomics: a scalable workflow to analyze large microbial genome collections - Le, DQ; Nguyen, TT; Nguyen, CH; Ho, TH; Vo, NS; Nguyen, T; Nguyen, HA; Vinh, LS; Dang, TH; Cao, MD; Nguyen, SH (BioMed Central, 2024)
Whole genome analysis for microbial genomics is critical to studying and monitoring antimicrobial resistance strains. The exponential growth of microbial sequencing data necessitates a fast and scalable computational pipeline to generate the desired outputs in a timely and cost-effective manner. Recent methods have been implemented to integrate individual genomes into large collections of specific bacterial populations and are widely employed for systematic genomic surveillance. However, they do not scale well when the population expands and turnaround time remains the main issue for this type of analysis. Here, we introduce AMRomics, an optimized microbial genomics pipeline that can work efficiently with big datasets. We use different bacterial data collections to compare AMRomics against competitive tools and show that our pipeline can generate similar results of interest but with better performance. The software is open source and is publicly available at https://github.com/amromics/amromics under an MIT license.